Effect of ginger endophyte Rhizopycnis vagum on rhizome bud formation and protection from phytopathogens. (April 2018) - Anisha, C.; Jishma, P.; Bilzamol, V. Sasi; Radhakrishnan, E.K.
Abstract: Most of the microorganisms residing within the plants are likely to be beneficial to the host plants as they either inhibit phytopathogens or promote plant growth. In the current study, endophytic fungal isolate from Zingiber officinale Rosc. with antagonism to soft rot pathogen Pythium myriotylum was investigated for its broad antiphytopathogenic properties. The crude extract prepared from the organism was found to have activity against various phytopathogens which was confirmed by scanning electron microscopic analysis. The isolate was identified as Rhizopycnis vagum by ITS sequencing. Remarkably, during the rhizome protection studies, the organism was found to prevent P. myriotylum infection in ginger with associated enhancement in germination and bud development. Hence the result is indication of role of endophytic fungi as highly promising and broad spectrum plant probiotic agent. Highlights: Identification of an endophytic fungus Rhizopycnis vagum from Zingiber officinale. R. vagum effectively protected ginger rhizomes from soft rot. Enhancement in germination and bud development in R. vagum treated ginger rhizome.